In vitro effects of 2-methoxyestradiol, an endogenous estrogen, on MCF-12A and MCF-7 cell cycle progression - Lottering, Mona-Liza (University of Pretoria, 2013)
Dissertation (MSc (Physiology))--University of Pretoria, 2008.